2004
DOI: 10.1097/01.brs.0000133643.75795.ef
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Lateral Transpsoas Approach to the Lumbar Spine

Abstract: Early results show the endoscopic lateral transpsoas approach to the lumbar spine to be a safe, minimally invasive method for anterior fusion of the first through the fourth lumbar vertebrae. Although there is a risk of groin/thigh numbness or pain, and these symptoms are mostly transient. This approach allows for exposure of the lumbar spine without mobilization of the great vessels or sympathetic plexus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(94 citation statements)
references
References 22 publications
0
89
0
Order By: Relevance
“…2,3,7,15 These tumors can be either intradural, extradural, or both. Rarely, these tumors arise within the lumbar plexus in the retroperitoneum as in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,7,15 These tumors can be either intradural, extradural, or both. Rarely, these tumors arise within the lumbar plexus in the retroperitoneum as in this case.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,13 A lateral transpsoas approach, as popularized in lateral interbody fusion surgery, is the most direct technique to approach retroperitoneal lumbar plexus tumors and should help to reduce postoperative pain and hospital stays and expedite the return to activities of daily living. [6][7][8][13][14][15] Furthermore, such an approach precludes the need for an access surgeon. 13 In this report, we describe a direct lateral minimally invasive approach to the retroperitoneum utilizing a tubular retractor and directional electromyography (EMG) for complete resection of an L4 nerve root schwannoma distal to the dorsal root ganglia in the psoas muscle.…”
mentioning
confidence: 99%
“…The major unique risk is injury to the lumbar nerves as they exit the neural foramen and travel through the psoas muscle forming the lumbosacral plexus. This can lead to complications related to pain, neuropraxia, and weakness [3,15,32]. Recent studies have identified complication rates ranging from 6.2% to 52% [4, 7, 13-16, 20, 26, 27, 32-34, 36].…”
Section: Introductionmentioning
confidence: 99%
“…4,9 One recent literature review has frequently been misreferenced to claim that motor weakness resulting from lumbar plexus injuries occurs in up to 33.6% of reported LLIF cases. 1 However, the purpose of the review was to advocate for a standardized classification of neurological findings after LLIF, and the motor weakness figure encompassed patients with transient iliopsoas weakness that occurs as results of muscle dissection by the retractor.…”
Section: Lumbar Plexus Risk From Lateral Access At L4-5mentioning
confidence: 99%